Ecoturismo en el Cerro Villonaco alto como complemento al turismo de la Central Eólica Villonaco - Naranjo Coronel, Luis Gustavo (2023)
This research work was conducted in order to generate ecotourism in the Villonaco hill, located southwest of the city of Loja in the limits of the canton Loja and Catamayo, being the most visited natural resource in the city of Loja, the proposal was proposed to complement the tourism generated in the Wind Power Plant. This consisted of an ecotourism diagnosis of Villonaco Hill and its surroundings, analysis of the demand of our potential visitors with a survey, and finally generate strategies to develop ecotourism in the place. In order to develop the objectives, the hill and its surroundings were evaluated internally and externally, applying Carla Ricaurte's cards, hierarchy cards of tourist attractions, thus determining the tourist potential of the area for ecotourism; in the second objective, a survey of 17 questions with preferences of the potential demanders in this type of tourism was conducted, these were applied in the Villonaco Wind Farm in person, nearby communities and via online. Finally, the third objective generated key strategies to develop ecotourism in Villonaco Hill and its surroundings, in addition to a SWOT and strategic SWOT analysis with the information from the results of objectives 1 and 2, resulting in 5 strategies, which propose different products and key activities for ecotourism in the area. Defining that the high Villonaco hill has characteristics to generate ecotourism based on areas for leisure activities, infrastructure, in addition to the natural wealth and rural tourism in nearby communities, then a demand that seeks new types of natural tourism to be developed once the 5 proposed strategies are implemented with the surrounding communities involved with the ecotourism project.